Dark Tourism Motivations, Experience, Emotions and Behaviour of Tourists - Hafizullah DAR; Amolakdeep KAUR (African Journal of Hospitality, Tourism and Leisure, 2024)
The purpose of this study is to explore travel motivations at dark tourism sites and the impact of dark tourism motivations on tourist experience. The study also tried to examine the impact of experience on tourist emotions and behaviour at dark tourism sites. The study was concluded by randomly surveying 400 respondents’ responses to the study instrument at Jallianwala Bagh, Amritsar-India. The study results revealed that curiosity, remembrance and knowledge are key travel motivations of tourists at dark tourism sites. Regression analysis determined that these travel motivations have a significant impact on cognitive and affirmative travel experiences of tourists. Further, the results showed that the cognitive and affirmative travel experiences of tourists positively influence tourist emotions and behaviour. These findings signify the importance of Jallianwala Bagh’s historical massacre among the visitors. This study enhances the existing knowledge of dark tourism as no such prior research was available to showcase the connotation among motivations, cognitive and affirmative experience, emotions and behaviour of tourists. The planners can use this study for destination development, marketing, and community engagement as well.